The efficiency of PBPC collections and the relationship to the precollection concentration of CD 34+ cells in blood - Gasová, Z; Marinov, I; Hrubá, A; Benesová, K; Turek, P (Transfusion science, 1999)
Transplantations of peripheral blood progenitor cells (PBPC) are able to assure a complete haematopoietic and immunologic reconstitution. The efficient mobilization of progenitor cells into peripheral blood is the main factor responsible for quality of the graft as well as timing and technique of collections. The aim of the present paper was to find the optimum time for starting PBPC collections and consequently to minimize the number of procedures required. The study was performed in patients with haematological malignancies using an autologous collection regimen. We attempted to determine a relationship between the concentration of CD 34+ cells in peripheral blood at the beginning of the collection and the number of CD 34+ cells in the leukapheresis product prepared in the standard mode processing 2-3 total blood volumes. We assessed the significance of the CD 34+ cells concentration in peripheral blood for the adequate collection of CD 34+ cells. We also evaluated the time of engraftment in patients after autologous PBPC transplantation whenever possible. The study was performed in 70 patients. Two groups were defined: Group I patients were well mobilized, whereas Group II patients were weakly mobilized. CD 34+ counts, using flow cytometry were found to be useful in predicting the optimal time for collections.
Keywords: Tissue and Organ Harvesting; příprava pacienta k transplantaci; Blood Specimen Collection; Hematopoietic Stem Cell Transplantation; Stem Cells; Time Factors; Transplantation Conditioning; transplantace hematopoetických kmenových buněk; kmenové buňky; antigeny CD34; Antigens, CD34; Humans; odběr tkání a orgánů; odběr vzorku krve; lidé; časové faktory